Ritual with a Little Interaction and Grammar with a Small Vocabulary: Exploring 'Afterwords' with Collins and Lindbeck. Issue 1 (June 2018) - Grant, Rhiannon
Abstract : This article explores the results of an online survey about the British Quaker use of 'afterwords' – a period of semi-programmed sharing or discussion after unprogrammed worship. It uses interaction ritual theory as created by Randall Collins and cultural-linguistic approaches to religion as theorised by George Lindbeck to discuss the ways in which British Quakers are using and reacting to 'afterwords'. In particular, it considers the reasons why 'afterwords' are coming into use and the polarising effect this practice seems to have on the community. It concludes by offering a suggestion about what may be underlying current observations about 'afterwords'.